Stres Akademik dan Prokrastinasi Akademik Pada Mahasiswa Bekerja - Wardani, Ari Fanti; Pratikto, Herlan; Suhadianto, Suhadianto (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2024)
Academic procrastination is the behavior of delaying work on assignments which is carried out intentionally and has a negative impact on students which can harm their abilities. However, it can also reduce stress, even if only temporarily. This research aims to determine the relationship between academic stress and academic procrastination in working students. Participants in this research were 205 evening class students from the class of 2023-2024 using incidental sampling techniques. The instruments used in this research were the Tuckman Procrastination Scale (TPS) which was adapted from Tuckman (1991) and the academic stress scale which refers to the theory of Bedwy and Gabriel (2015). The results of the product moment correlation test show that the relationship between academic stress and academic procrastination obtained a correlation of rxy = 0.764, significance of p = 0.000 (p<0.05), which means that there is a significant positive relationship between academic stress and academic procrastination in working students. These results indicate that the higher the academic stress, the higher the academic procrastination in working students. The statement above states that the hypothesis in this research is accepted. Prokrastinasi akademik merupakan perilaku penundaan dalam mengerjakan tugas yang dilakukan secara sengaja dan berdampak buruk pada mahasiswa yang dapat merugikan kemampuannya. Namun juga dapat mengurangi stres meskipun hanya bersifat sementara. Penelitian ini bertujuan untuk mengetahui hubingan antara stres akademik dengan prokrastinasi akademik pada mahasiswa bekerja. Partisipan pada penelitian ini adalah 205 mahasiswa kelas sore angkatan 2023-2024 dengan menggunakan teknik sampling incidental. Instrument yang digunakan dalam penelitian ini adalah Tuckman Procrastination Scale (TPS) yang diadaptasi dari Tuckman (1991) dan skala stres akademik yang mengacu pada teori Bedwy dan Gabriel (2015). Hasil uji korelasi product moment bahwa hubungan stres akademik dengan prokrastinasi akademik memperoleh korelasi rxy = 0,764 signifikasi sebesar p = 0,000 (p<0,05) yang berarti adanya hubungan positif signifikan antara stres akademik dengan prokrastinasi akademik pada mahasiswa bekerja. Hasil ini menunjukkan bahwa semakin tinggi stres akademik maka semakin tinggi prokrastinasi akademik pada mahasiswa bekerja. Pernyartaan diatas menyatakan bahwa hipotesis dalam penelitian ini diterima.